2021
DOI: 10.1021/acs.est.1c02704
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of Enhanced Photoreactivity of Dissolved Organic Matter after Chlorination

Abstract: Chlorine is commonly used in disinfection processes in wastewater treatment plants prior to discharge of the effluents into receiving waters. Effluent organic matter and humic substances constitute up to 90% of dissolved organic matter (DOM) in receiving water, which induces photogeneration of reactive species (RS) such as excited triplet state of DOM ( 3 DOM*), singlet oxygen ( 1 O 2 ), and hydroxyl radical ( • OH). The RS plays an important role in the attenuation of trace pollutants. However, the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…Previous work found that the amount of terrigenous DOC mineralized by photodegradation is higher in the ocean than in inland waters. 11 Increasing concentrations of halides, 50,51 higher pH, and increased penetration of ultraviolet radiation 52 enhance DOM photobleaching in the coastal ocean. Our work also suggests that aged DOM is more vulnerable to photobleaching based on the observation that CDOM photobleaching rates increased slightly with DOM aging in irradiation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work found that the amount of terrigenous DOC mineralized by photodegradation is higher in the ocean than in inland waters. 11 Increasing concentrations of halides, 50,51 higher pH, and increased penetration of ultraviolet radiation 52 enhance DOM photobleaching in the coastal ocean. Our work also suggests that aged DOM is more vulnerable to photobleaching based on the observation that CDOM photobleaching rates increased slightly with DOM aging in irradiation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…After ruling out the contribution of Fe­(III) and TPP substitution to the Cu­(II)-EDTA decomplexation in the Na 6 TPP-EF process, we thus investigated the roles of ROS, which might destruct the Cu­(II)-EDTA bonds to release Cu­(II) ions. The •OH and •O 2 – radicals were measured using the DMPO spin-trapping ESR spectra at pH 7.5 in deionized water and methanol solution, respectively. ,, A typical •OH signal was observed at 10 min during the Na 6 TPP-EF process, and the time-dependent enhanced signals demonstrated the gradual accumulation of •OH radicals during the reaction (Figure b). In contrast, the signals of the DMPO-•O 2 – spin adduct were weakened along with the reaction (Figure c) .…”
Section: Resultsmentioning
confidence: 94%
“…As generally known, DOM acts as a UV filter, consumes HOCl/OCl – ( k = (0.7–5) M c –1 s –1 ), and is a typical radical scavenger of HO· and RCS (details shown in the Supporting Information). ,, In addition, antioxidant moieties in DOM can reduce intermediate radicals of contaminants back to their parent compounds. , Meanwhile, DOM can promote the abatement of some contaminants, as it can generate 3 DOM*, 1 O 2 , and HO· under UV or solar irradiation . All these reactions involving DOM can alter the radical chemistry in UV/chlorine (Figure S2), while the related knowledge is still limited.…”
Section: Radical Chemistry Of the Uv/chlorine Processmentioning
confidence: 99%